Development and in vitro characterization of esomeprazole floating gastro retentive microspheres - Prakash Goudanavar, Shashikanth Reddy, Doddayya Hiremath and Rajgopal Udupi (Journal of Applied Pharmaceutical Science, 2013)
The present study was to prepare and evaluate the floating microspheres of Esomeprazole magnesium trihydrate as a model drug for prolongation of the gastric retention time for oral delivery. EMT is a proton pump inhibitor which acts by irreversibly blocking the (H+K+)-ATPase enzyme system of the gastric parietal cell. Its half life is 1-1.5 hrs. EMT poor absorption may be because of degradation in gastric acid which can be prevented by incorporation of sodium bi carbonate which is a systemic antacid and act as buffer. The EMT floating microspheres were prepared by double emulsion solvent diffusion method by using Ethyl cellulose and different grades of HPMC like K4M, K15M, using Dichloromethane and alcohol solvent systems. EMT Floating microspheres were evaluated for micromeritic properties, particle size, % yield, In-Vitro buoyancy, incorporation efficiency and drug release. The prepared microspheres were found to be spherical and free flowing and remain buoyant for more than 10 hrs and the particle sizes of microspheres were found to be in the range of 67.24±4.57 μm to 106.35±5.67μm. Incorporation efficiency was found in the range of 54.75±3.51to 83.97±2.54. In-vitro release profile of optimized formulations follows first order non-Fickian (Anomalous) release indicates diffusion and dissolution controlled release. FT-IR and DSC studies revealed the absence of any chemical interaction between drug and polymers used. During the stability period selected microspheres were found to be stable with respect to Entrapment efficiency and drug release characteristics.
Keywords: Esomeprazole magnesium trihydrate, Ethyl cellulose,